Innovative forms of organizing : international perspectives - Pettigrew, Andrew M. (Andrew Marshall), 1944- (Sage Publications, 2003)
Sixteen international academics and researchers report findings from the Innovative Forms of Organizing (INNFORM) program, a collective endeavor of an international research network lead from Warwick Business School, UK, and involving six other European universities and one each from the U.